Comparison of Efficacy of Anti-interleukin-17 in the Treatment of Psoriasis Between Caucasians and Asians: A Systematic Review and Meta-Analysis - Zhang, Danyi; Qiu, Jianing; Liao, Xing; Xiao, Yi; Shen, Minxue; Deng, Yaxiong; Jing, Danrong (Frontiers in Medicine, 2022)
Background Interleukin-17 (IL-17) monoclonal antibody drugs have been increasingly significant in the treatment of psoriasis, but it is not clear whether the efficacy is equivalent across ethnicities. Objective To explore the differences of short-term efficacy of IL-17 inhibitors between Caucasians and Asians. Methods The pooled log risk ratio (logRR) between the groups was estimated. The meta-regression analysis on the logRR was performed, with the proportion of Caucasian patients as the covariate. The subgroup analysis was performed by specific IL-17 inhibitors. Results Of the 1,569 potentially relevant studies, sixteen randomized controlled trials (RCTs) were included. For the Psoriasis Area and Severity Index 75 (PASI 75) response at week 12, the pooled logRR of the Asian group and the Caucasian group was 2.81 (95% CI: 2.27–3.35, p < 0.001) and 2.93 (95% CI: 2.71–3.16, p < 0.001), respectively, indicating no significant difference of efficacy between Asians and Caucasians. The meta-regression analysis did not show an association of the proportion of Caucasians with the effect size (β = 0.3203, p = 0.334). In the subgroup analysis, the comparison results of secukinumab were consistent with the main analysis. Limitations Only the short-term efficacy was explored. The data from Asian countries were limited. Conclusions The short-term efficacy of IL-17 inhibitors in the treatment of psoriasis has no significant difference between Caucasians and Asians. Systematic Review Registration PROSPERO, identifier CRD42020201994, https://www.crd.york.ac.uk/prospero/.